OPTIMALISASI MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN MUTU PEMBELAJARAN : Penelitian di MTs Darul Irfan Padarincang - Inayatulloh, Siti; Nurhakim, Muhamad Syara (Staisman Press, 2021)
This research was conducted to find out 1) How infrastructure is planned to improve the quality of education. 2) How to use infrastructure to improve the quality of education. 3) How to control infrastructure to improve the quality of education. 4) How to evaluate infrastructure in improving the quality of education. 5) What are the inhibiting and supporting factors of infrastructure and 6) What are the solutions to overcome obstacles to optimizing the use of educational infrastructure to improve the quality of education. The research uses qualitative research methods with a phenomenological approach. Data collection techniques are by means of observations, interviews, document studies using recording facilities and data notes. The results of the research show that the management of infrastructure at MTs Darul Irfan Padarincang is not very good and requires improvements in planning, use, control and evaluation, and there are two inhibiting factors 1) foundation, 2) school committee and solutions.